PENATALAKSANAAN ASUHAN PADA IBU POSTPARTUM BLUES DI KLINIK MANDA MEDAN - Elvalini Warnelis Sinaga; Risa Tantry Gultom; Eva Nirwana Hutabarat (Jurnal Ilmiah Kebidanan Imelda, 2024)
Postpartum blues Approximately 70-80% of post-partum mothers experience mood or feeling disorders, in general this condition is still considered normal, is felt from 2-3 days after giving birth and normally disappears after 2 weeks postpartum. This study provides comprehensive midwifery care for pregnant women, maternity, postpartum, BBL, neonates and family planning using a midwifery management approach to Ny. “D” with the case of the ASI Dam. Care in this study with observation and evaluation. The subject of this care is Mrs. “D” with POSTPARTUM BLUES at Manda Clinic. This research activity is about the handling of POSTPARTUM BLUES in postpartum mothers. The study conducted observations and evaluations of mothers on a regular basis. Observations and evaluations were carried out not only assessing but knowing and assessing the conditions and support for mothers. Husbands and parents are also needed to support mothers. This research was conducted at the Manda Clinic.Factors that cause the appearance of signs and symptoms of the postpartum blues. The results showed that age and parity were not always the triggering factors for postpartum blues symptoms, the causes of postpartum blues were worrying about the baby, maternal fatigue factor, comments from people around about the mother, husband's support and presence, adaptation to the baby's presence.